Anti-fibrotic role and mechanism of Periplaneta americana extracts in CCl4-induced hepatic fibrosis in rats. (12th March 2018) - Li, Dingchun; Li, Wu; Chen, Yihui; Liu, Lihui; Ma, Dehong; Wang, Hongtu; Zhang, Lu; Zhao, Shenjun; Peng, Qin
Abstract: Hepatic fibrosis is resulted from sustained wound-healing responses to various harmful stimuli, including viral infection, drug toxicity, alcohol, and autoimmune hepatopathy, and it has recently attracted the attention of an increasing number of researchers and clinical workers. The aims of this study were to examine the anti-fibrotic effects of extracts of Periplaneta americana (EPA) on CCl4 -induced hepatic fibrosis in rats, to preliminary determine the anti-fibrotic efficacy of EPA, and to identify a potential and effective therapeutic agent to attenuate hepatic fibrosis. In this study, we routinely detected liver functional indices, such as alanine aminotransferase (ALT), aspartate transaminase (AST), and albumin (Alb). We also measured hepatic fibrosis-related serum markers, including hyaluronic acid (HA), laminin (LN), type III procollagen (PC III), and type IV collagen (IV-C) via radioimmunoassay. Moreover, we examined histological activity and fibrosis stage via light microscopy after hematoxylin and eosin and Masson staining. Furthermore, we detected the expressions of nuclear factor-kappa B (NF-κB), alpha-smooth muscle actin (α-SMA), transforming growth factor-β1 (TGF-β1), and tissue inhibitor of metalloprotease-1 (TIMP-1) in rat liver tissues by immunohistochemical staining. We found that EPA, whose main components are viscous sugar amino acids, can reduce the levels hepatic fibrosis-related factors, including HA, LN, PC III, and IV-C, improve liver function, attenuate, or reverse pathological damage associated with hepatic fibrosis, and thus inhibit the progression of hepatic fibrosis. The mechanism of EPA action may be related to the inhibition of TGF-β1, NF-κB, and α-SMA expressions and the reduction of TIMP-1 levels in the liver to reduce the accumulation of extracellular matrix (ECM) components, thereby blocking the relevant signaling pathways and preventing inflammatory responses to attenuate or reverse hepatic fibrosis. EPA may thus be used as a potentially effective therapeutic agent for the treatment of hepatic fibrosis.